2019
DOI: 10.1213/ane.0000000000004071
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Erector Spinae Plane Block in Patients Undergoing Open Epigastric Hernia Repair: A Prospective Randomized Controlled Study

Abstract: BACKGROUND: Hernia repair is associated with considerable postoperative pain. We studied the analgesic efficacy of bilateral ultrasound-guided erector spinae plane block in patients undergoing open midline epigastric hernia repair (T6–T9). METHODS: Sixty patients 18–65 years of age were randomly allocated into 2 groups. Patients in the erector spinae plane block group received bilateral ultrasound-guided erector spinae plane block at the level of T7 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 15 publications
1
79
0
1
Order By: Relevance
“…Rebound pain is a phenomenon that primarily manifests following PNB that provide dense sensory blockade (e.g., brachial plexus [2,7,10], popliteal sciatic [3,9] nerve blocks). Dramatic increases in pain scores and opioid consumption related to block offset are not usually seen in studies of fascial plane blocks such as transversus abdominis plane [59], pectoral nerves [60], erector spinae plane, [61] and quadratus lumborum [62,63] blocks.…”
Section: Regional Anesthetic Techniquesmentioning
confidence: 98%
“…Rebound pain is a phenomenon that primarily manifests following PNB that provide dense sensory blockade (e.g., brachial plexus [2,7,10], popliteal sciatic [3,9] nerve blocks). Dramatic increases in pain scores and opioid consumption related to block offset are not usually seen in studies of fascial plane blocks such as transversus abdominis plane [59], pectoral nerves [60], erector spinae plane, [61] and quadratus lumborum [62,63] blocks.…”
Section: Regional Anesthetic Techniquesmentioning
confidence: 98%
“…Increasing cases of ultrasound-guided erector spinae plane block appeared in clinical applications [4,5]. At the same time, in order to demonstrate the effect of ultrasound-guided ESP block, many clinical randomized controlled trials (RCT) have been conducted [3,[6][7][8][9][10][11]. Tulgar et al [6] confirmed that bilateral ultrasound guided ESP block leads to effective analgesia and reduce analgesia requirement in first 12 h in patients undergoing laparoscopic cholecystectomy (LC).…”
Section: Backgroudmentioning
confidence: 99%
“…Whether ESP blocks can be effectively used in thoracoscopic surgery is still in dispute. Some reports have indicated [6,11,18] ESP blocks can be used for abdominal surgery.…”
Section: Fig 2 Marked Lines and Pointsmentioning
confidence: 99%
“…All RCTs [5][6][7][17][18][19][20][21][22][23][24][25] reported data on intravenous opioid consumption 24 h after surgery. Pooled analysis showed that ultrasound-guided ESPB was associated with a reduction of opioid 24 h after surgery (− 2.18, 95% CI − 2.76 to − 1.61; P < .00001; Fig.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Parietal pain is more prominent in breast and lumbar spine, while visceral pain is the main component of postoperative pain following abdominal surgeries. The use of different types of opioid and supplementary analgesics such as paracetamol [23,24] may also add an extra heterogeneity. Furthermore, owing to all patients were under GA surgeries, sensory blocking could not be evaluated adequately to exclude potential block failures of ESPB.…”
Section: Strengths and Limitationsmentioning
confidence: 99%